The Effect of Infant Massage on Mother-Infant Bonding Among Infants Aged 6-12 Months - Ririn Indriani; Finta Isti Kundarti (KHD Production, 2026)
Mother–infant bonding is a fundamental component of early emotional development and has long-term effects on infants’ behavioral, psychological, and neurodevelopmental outcomes. Infant massage is widely recognized as a complementary intervention that promotes parent–child interaction, facilitates emotional closeness, and enhances touch-mediated communication between mothers and infants. This study aims to investigate the effect of infant massage on bonding among infants aged 6–12 months. This research employed a quasi-experimental design with a pretest–posttest control group. The intervention included structured training using standardized massage techniques, followed by four weeks of home-based practice. Bonding was measured using the Maternal Infant Bonding Scale (MIBS) before and after the intervention. Data analysis used paired t-tests to assess within-group differences and independent t-tests to compare outcomes between the intervention and control groups. The results showed a significant improvement in bonding scores among mothers in the intervention group p-value = 0.011, with apparent differences compared to the control group. Observational data revealed enhanced maternal sensitivity, increased affectionate behavior, and greater emotional attunement. These findings suggest that infant massage is a practical, low-cost, and feasible intervention that can be effectively integrated into community-based maternal and child health programs to promote emotional attachment and support early developmental outcomes.